The new TanDEM-X DEM Change Maps Products - Lachaise, Marie; Gonzalez, Carolina; Rizzoli, Paola; Schweißhelm, Barbara; Zink, Manfred (IGARSS 2022 - 2022 IEEE International Geoscience and Remote Sensing Symposium, 2022)
The Earth is a very dynamic system and the topographic height of its landmass changes over time, especially in forested areas, glaciers, permafrost regions or where human activities take place. After the TanDEM-X mission provided a first global DEM of unprecedented quality in 2016, a new complete coverage of the Earth's landmass was acquired mainly between 2017 and 2020. This data is used to create another global DEM. In addition to providing more up-todate elevation information, these new acquisitions also provide a great dataset to show the changes that have occurred in the few years between the two global datasets. The new product - the TanDEM-X DEM Change Maps - will be produced in 30m and 90m postings and will focus on showing these changes between the first global TanDEM-X DEM and the newly acquired time-tagged DEM scenes. It will also include the in-house automatically edited TanDEM-X DEM.